Formulation Of Ointment From Extract Combination Of Lemongrass (Cymbopogon nardus L. Rendle), Green Betel Leaf (Piper betle L.) And Natural Zeolite As An Antibacterial Agent - Laila Susanti; Subur Widodo; Mashuri Yusuf; Retno Fardila Sari (Biota, 2020)
Lemongrass (Cymbopogon nardus L. Rendle) and green betel (Piper betle L.) plants are native to Indonesia. Empirically betel leaf can be used as a wound healer, lemongrass leaves are widely used as medicine for insect bites. On the basis of information obtained from various literatures, in this research has been done formulation of ointment from extract combination of lemongrass, green betel leaf and natural zeolite as antibacterial of Staphylococcus aureus. The use of zeolites based on features has a three-dimensional framework structure that is interconnected so that it has a large surface. Based on these reasons, it is believed that zeolites can increase the activity of active substances in ointments. The formulation of ointment extracts of lemongrass leaves-green betel leaves and zeolites with various dosages are KZ (zeolite control), KE (20% -5%), F1 (10% -6% + zeolite), F2 (20% - 5% + zeolite), F3 (30% -4% + zeolite), F4 (20% -0% + zeolite), F5 (0% -5% + zeolite) with a fixed amount of zeolite (2 gr). Evaluation of ointment preparations including organoleptic test, pH, homogeneity, spreading test and adhesion test showed results that met the requirements. The sample was tested for antibacterial activity with positive control (gentamicin 0.1%) showed that all formulas can provide an inhibition zone against staphylococcus aureus, except KZ. Test results were analyzed using One Way Annova with sig (0,000) <p value (0,050) followed by Tukey's further tests. From this explanation it can be concluded that the formulation of ointment from extract combination of lemongrass leaves, green betel leaves and zeolites has antibacterial agent.